CONSUMER PREFERENCY AND STORE ENERGY OF STAFFY MADE OF BARK - Heni Purwaningsih; Siti Raharu; Nur Hidayat; Niniek Kusuma Wardhani (Fakultas Pertanian, Universitas Janabadra, 2005)
Research have been done of making taffy made of bark by three type bark that were bark of pondoh, bark of pondoh non grade and local bark. Staffy made of bark which very like by consummer is staffy made pondoh bark non grade. Furthermore staffy made pondoh bark non grade have been done store with two treatment without preservative addition (A) and preservative addition of natrium benzoat 0,1% (B). Used Complete Random Device design with one factor and with the different test Downright Reality (BNJ) 5% real level with three replication. Result of research showed that be based on organoleptic test include : colour, aroma, taste and texture, staffy made of pondoh bark non grade without preservative have store energy 18 day, while staffy made bark by preservative natrium benzoat 0,1% having store energy 45 day. Result of Analysis peroxide number showed that existence tendency of increase during stored